Partocracy or Democracy: A Popperian Perspective of Democracy in Albania - Ibraimllari, Suela (European Journal of Multidisciplinary Studies, 2017)
"If the idea of democracy is sustainable, its implementation is uncertain, " says Cister, in order to highlight the fact that, despite efforts of different societies to consolidate their democracy, the democracy as a governance system, continues to be at risk. In this context, this research paper aims to identify, argue and analyze the level of the Albanian democracy development, which is consolidating a declined democracy system, that of partocracy. To develop this discussion, we are focused on the examination and recognition of the above two systems, which in terms of Albanian democracy, put in front of each-other, two theses in the field of political philosophy, that of Karl Popper and Mauro Calise. The comparison and recognition of these philosophical theses will guide the study of Albanian model of democracy. This discussion will go through philosophical theses, based on indicators of democracy that are: pluralism, voting system and decentralization of powers.
Keywords: partocracy, “Popperian democracy”, pluralism, voting system, institutional decentralization.